Strategi Political Public Relations Partai Solidaritas Indonesia wilayah Riau pada Pemilihan Legislatif tahun 2019 - Muhammad Tazri; Desy Mairita (Communiverse : Jurnal Ilmu Komunikasi, 2019)
This research elaborates on the Political public relations strategy carried out by the novice politicians of the Indonesian Solidarity Party in the Riau region in the face of the 2019th Legislative Elections. This research is important because the Indonesian Solidarity Party (PSI) is a new party and politicians who participate in political contestation are also novice politicians. This research is a descriptive qualitative research with case study method, data retrieval through the stages of observation, interviews and documentation. The results of this study reveal that the Political public relations strategy undertaken by PSI politicians is by combining image building, political branding and political marketing.